EFFECT OF KARAMUNTING LEAF EXTRACT (Melastoma malabathricum L.) ON GLUCOSYLTRANSFERASE ENZYME OF Streptococcus mutans - Ferdy Juliannor Fajar; Deby Kania Tri Putri; Bayu Indra Sukmana (FKG Unlam, 2020)
ABSTRACTBackground: Karamunting leaf extract has secondary metabolite compounds such as tannin, flavonoid, and phenol that have antibacteria potential to be used as an alternative to mouthwash in addition to Chlorhexidine 0.12% to lower the incidence of tooth caries. Caries is caused by several important virulence factors, including Streptococcus mutans Glucosyltransferase (GTF) enzyme. Karamunting leaf extract can inhibit the work of GTF enzyme by precipitating, denaturing protein and damaging cell walls. Inhibition of Streptococcus bacteria enzyme activity will decrease plaque formation, thus decreasing the potential of dental caries. Objective: The purpose of this study was to determine the effect of Karamunting leaf extract and 0,12% Chlorhexidine on Glucosyltransferase enzyme activity of Streptococcus mutans. Methods: This study used true experimental design with post test only with control group design using 7 groups, including Karamunting leaf extract group with 5%, 10%, 15%, 20%, and 25% concentrations to determine the activity of S. mutans GTF enzyme. Results: The results showed that Karamunting leaf extract with 20% concentration was able to decrease the activity of Glucosyltransferase enzyme in Streptococcus mutans. Conclusion: Karamunting leaf extract affects Streptococcus mutans Glucosyltransferase enzyme activity. Keywords: Chlorhexidine 0,12%, Glucosiltransferase, Melastoma malabathricum L., Streptococcus mutans.